Instantiating and Monitoring Skeletal Treatment Plans - Uckun, S. (Methods of Information in Medicine, 1996)
Current emphasis on protocol-based care has stirred interest in planning research as applied to clinical medicine. However, many assumptions made in designing traditional planners and plan-execution algorithms do not hold in medical domains. The problems include the unpredictable nature of the domain, uncertainty and the variability in the utility of available actions, and the need for parallel and continuous execution of treatment plans. In the context of our research on intelligent monitoring and control, we developed an approach for plan instantiation and execution which takes advantage of readily available treatment protocols. The system, named SPIN, instantiates treatment protocols based on current context, executes plans and closed-loop control actions, monitors the execution of plans and actions, and modifies plan execution as necessitated by patient response. The system is incorporated in the Guardian system for intensive-care patient monitoring and control. We address the strengths and limitations of the representation and the execution framework and discuss how the methodology may be improved and used in clinical practice.
Keywords: Protocol-based Treatment; Treatment Planning; Monitoring